Neo-Sufisme Syaikh Abd Al-Karim Dan Gerakan Perlawanan Anti Kolonialisme Di Banten - Kesuma, Arsyad Sobby; Hakiki, Kiki Muhamad; Tauhid, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research examines the motivation of tarekat followers who were mostly involved in a rebellion of the people of Banten, during the Dutch colonial period. Based on the results of the research, it is concluded as follows: First, Tarekat Qadiriyah wa Naqsyabandiyah was introduced by Haji Abdul Karim in the mid-19th century. This order had a considerable influence, both among the farmers and among the officials. Because of its strong influence, the Banten area in a short time was colored by an extraordinarily active religious life. So great was the influence of the Tarekat leader in Banten, that he was able to mobilize the masses of people who needed a leader who could restore the integrity of the village. Secondly, the rebellion spearheaded by kyai, hajj, and tarekat teachers showed that the ulama did not agree with the ideas put forward by the Dutch government. for the sake of the peace of religious life in Banten, the last alternative was to expel the colonizers from Banten. Their involvement in a rebellion aimed to establish an Islamic state (dar al-Islam), the penetration of colonial domination that contradicted the religious life in Banten.